Political Promotion, Ceo Compensation, and Their Effect on Firm Performance - CAO, Xiaping Jerry (Institutional Knowledge at Singapore Management University, 2009)
We investigate the impact of CEO’s compensation-based and promotion-based incentives on firm performance in China, where the CEOs of most state-owned enterprises are government appointed and thus face dual incentives. We find that both monetary and political incentives are positively related to firm performance. More important, we pinpoint a substitution effect: the monetary compensation-based incentive is weaker when CEO incentives are heavily driven by political career concerns. Overall, the evidence suggests that, via a competitive arena in the external political job market, promotion helps mitigate weak incentives for CEOs in China. State control or political connection is not necessarily inconsistent with good economic incentives.